2021
DOI: 10.1002/hep.31616
|View full text |Cite|
|
Sign up to set email alerts
|

HBV RNA Profiles in Patients With Chronic Hepatitis B Under Different Disease Phases and Antiviral Therapy

Abstract: Background and Aims Large‐scale comprehensive studies on HBV RNA in chronic hepatitis B are lacking. We aimed to study the HBV RNA profile and its correlation with other viral markers in patients with chronic hepatitis B who are treatment‐naïve and patients receiving nucleos(t)ide analogues (NA). Approach and Results Biomarkers, including HBV RNA and hepatitis B core‐related antigen (HBcrAg), were measured in 388 patients. Of these, 246 were treatment‐naïve and were categorized into HBeAg‐positive chronic infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
91
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(99 citation statements)
references
References 29 publications
7
91
1
Order By: Relevance
“…Second, our study was conducted based upon the tertiary referral hospital‐based cohort, and its results are potentially subject to selection bias. Third, the use of new biomarkers (eg serum quantitative HBsAg, serum hepatitis B core–related antigen, serum HBV RNA or specific HBV mutants), which can reflect the clinical course of CHB, would have provided the more precise prediction 52–57 …”
Section: Discussionmentioning
confidence: 99%
“…Second, our study was conducted based upon the tertiary referral hospital‐based cohort, and its results are potentially subject to selection bias. Third, the use of new biomarkers (eg serum quantitative HBsAg, serum hepatitis B core–related antigen, serum HBV RNA or specific HBV mutants), which can reflect the clinical course of CHB, would have provided the more precise prediction 52–57 …”
Section: Discussionmentioning
confidence: 99%
“…Many studies have evaluated the correlation between HBV RNA and other traditional or novel HBV biomarkers to investigate HBV natural history and determine the utility of serum HBV RNA as an alternative biomarker. In treatment-naïve patients within multi-ethnic cohorts, it has been shown that levels of serum HBV RNA are higher in HBeAg-positive CHB patients than in those who are HBeAg-negative [ 22 , 29 , 39 , 40 , 41 ]. Additionally, a strong correlation between serum HBV DNA and serum HBV RNA levels in treated and untreated patients has been reported [ 22 , 32 , 40 , 42 ].…”
Section: Novel Hbv Biomarkersmentioning
confidence: 99%
“…Additionally, a strong correlation between serum HBV DNA and serum HBV RNA levels in treated and untreated patients has been reported [ 22 , 32 , 40 , 42 ]. However, this correlation has not been consistently observed in treatment-naïve patients [ 39 , 43 ]. Serum HBV RNA was also found to correlate with HBcrAg [ 39 ] and moderately correlate with HBsAg and HBeAg quantities [ 40 ] in treatment-naïve patients.…”
Section: Novel Hbv Biomarkersmentioning
confidence: 99%
“…maintenance of viremia) or to maintain the level of cccDNA following recycling of rcDNA to the nucleus, 9 careful/close monitoring of viremia using very potent qPCR technology has demonstrated partial virologic responses in longterm NA-treated patients, with viremia varying between "non detectable" and very low levels. 10 This indicates that the blockade of HBV Pol activity is not 100%. This also has consequences for cccDNA levels, as residual HBV Pol activity might be sufficient to maintain the cccDNA pool.…”
Section: Improvements To Currently Used Nas?mentioning
confidence: 99%